Effect of freezing and thawing on ejaculated sperm and subsequent pregnancy and neonatal outcomes in IVF - Xie, Qin; Jiang, Xueyi; Zhao, Ming; Xie, Yating; Fan, Yong; Suo, Lun; Kuang, Yanping (Frontiers in Endocrinology, 2024)
The techniques of sperm cryopreservation exhibit its potential in male fertility preservation. The use of frozen-thawed sperm in in vitro fertilization (IVF) cycles is widespread today. However, many studies reported that cryopreservation might have adverse effects on sperm DNA integrity, motility, and fertilization, probably due to cold shock, intra-and extracellular ice crystals, and excess ROS. Studies suggested that the freezing and thawing process impaired sperm viability but might adversely affect subsequent fertilization and pregnancy outcomes. The potential damage to fertilization and subsequent embryonic development and offspring health raises the concern of sperm cryopreservation. However, the above-mentioned studies are limited to intracytoplasmic sperm injection (ICSI) cycles, while IVF is a more natural and patient-friendly method. IVF requires a higher quality of sperm than ICSI. However, the effect of freezing and thawing on sperm used for IVF remained unknown. Therefore, we aim to investigate the effect of freezing and thawing on ejaculated sperm and subsequent pregnancy and neonatal outcomes in IVF. This retrospective cohort study at a tertiary-care academic medical center included 447 women using paternal frozen-thawed ejaculated sperm and 31039 women using paternal fresh ejaculated sperm for IVF and undergoing followed frozen-thawed blastocyst transfer from January 2011 to September 2021. To balance the baseline characteristics of the two groups, patients using frozen sperm were matched with control groups using a propensity score matching algorithm in a ratio of 1:3. Although the sperm motility decreased from 82.04% to 75.70% (P<0.001) after freezing-thawing process, the fertilization rate (68.27% for frozen sperm and 67.54% for fresh sperm), number of viable embryos (1.98 and 2.16), clinical pregnancy rate (44.7% and 51.8%) and live birth rate (40.3% and 42.4%) were comparable between two groups (all P>0.05). For neonatal outcomes, no between-group differences were observed in offspring gender, gestational age, birthweight, and the rate of preterm birth (21.7% and 12.9%), low birthweight neonates (19.2% and 16.0%), and birth defects (0.0% and 0.8%) (all P>0.05). Frozen-thawed sperm had lower sperm motility but resulted in comparable embryonic, pregnancy, and neonatal outcomes versus fresh sperm in IVF cycles.